Reliability in Single Domain vs. Multi Domain Optical Mesh Networks - Akyamac, A. A.; Sengupta, Sudipta; Chaudhuri, Surajit (National Fiber Optic Engineers Conference (NFOEC) 2002, Dallas (USA), 2002)
Network reliability is an important element of a service level agreement and is typically evaluated based on the number of unavailable minutes per year. The widespread belief is that networks with faster restoration times are more reliable, created by the assumption that fast restoration from a failure leads to smaller down time. This is not necessarily the case since it has been shown that reliability may have little to do with the restoration speed when the restoration time is small compared to the mean time to repair of the failed elements. In this paper, we compare the reliability of optical mesh networks with multi domain restoration and single domain restoration using both dedicated mesh protection and shared mesh restoration, and show that splitting a network into multiple domains increases the overall reliability.